Role of Youth in the Promotion of Good Governance in Pakistan - Dr. Sarwat Rauf (Journal of Political Studies, 2019)
This paper aims to examine the role of youth in the promotion of good governance in Pakistan. It highlights the importance of youth for Pakistan‟s development. Almost 60% of the country‟s population is young and they have the potential to bring prosperity and good governance. The development of Pakistan is in the hands of the country's energetic and talented youth. However, fewer opportunities, the dearth of proper supervision and lack of capacity to absorb true/untrue information are misguiding them. Very few of our youngsters know the technique to utilize time and positive energies excellently. This paper focuses that psychologically vulnerable youth can be an easy prey of criminals. Today, the problem of our large number of youngsters is, they are with no work and their energies are turning into destruction and crimes. In this backdrop, this study endeavors to find the answer that how we can provide the right avenues to our youngsters to excel. The societal pressures and depression are causes of drug addiction in the teenagers. Thus, systemic involvement of youth is needed to build strong Pakistan; for this youth must be cognizant of national and international changes. In this regard, parenting plays important role. Moreover, for character building, educational institutions and media are effective tools. The formation of career counseling centers to guide our youth is indispensable. Without the training of today‟s youth, we cannot expect renowned scientists, engineers and future political leaders. Overall, it is focused that training/ counseling and employment opportunities must be prioritized so that intolerance and violence in the society can be curbed.